Psychological well-being pasangan pernikahan dini: Adakah Peranan Marital Adjustment? - Galuanta, Deviolla Anastazya; Meiyuntariningsih, Tatik; Aristawati, Akta Ririn (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
Psychological well-beingis the ability of individuals to accept their circumstances, form warm relationships with others, control their environment, be able to control the environment, have goals and develop talents and abilities for personal growth. One of the influencing factors psychological well-being marital adjustment were the more each individual early marriage couple can make adjustments to each other, the more they can achieve psychological well-beingThis study aims to determine the relationship between marital adjustment with psychological well-being for married couples who marry early. The hypothesis put forward in this study is that there is a positive relationship between marital adjustment with psychological well-being.This study uses quantitative methods to achieve research objectives. The subjects used in this study were early marriage couples in North Surabaya which was a research study snowball. Measuring tool using a scale marital adjustment(Hurlock 2002) and psychological well-being (Ryff 1989). The data obtained were analyzed using correlation techniques Spearman rho with the help ofSPSS 26 IBM for Macbook. Based on the results of the data analysis that has been done, it is found that there is a positive and very significant relationship between Marital Adjustments with Psychological well-being. Psychological well-being adalah kemampuan individu untuk menerima keadaannya, membentuk hubungan yang hangat dengan orang lain, mengendalikan lingkungannya, mampu mengontrol lingkungan, memiliki tujuan dan mengembangkan bakat dan kemampuan untuk pertumbuhan pribadi. Salah satu faktor yang mempengaruhi psychological well-being adalah marital adjustment yang dimana semakin masing-masing individu pasangan pernikahan dini bisa melakukan penyesuaian satu sama lain maka dapat bisa mencapai psychological well-being Penelitian ini bertujuan untuk mengetahui hubungan antara marital adjustment dengan psychological well-being pada pasangan suami istri yang melakukan pernikahan dini. Hipotesis yang diajukan dalam penelitian ini adalah ada hubungan positif antara marital adjustment dengan psychological well-being. Penelitian ini menggunakan metode kuantitatif untuk mencapai tujuan penelitian. Subjek yang digunakan dalam penelitian ini yaitu pasangan pernikahan dini yang berada di Surabaya Utara yang merupakan penelitian studi snowball. Alat ukur menggunakan skala marital adjustment (hurlock 2002) dan psychological well-being (Ryff 1989). Data yang diperoleh dianalisis dengan teknik korelasi Spearman rho dengan bantuan SPSS 26 IBM for Macbook. Berdasarkan hasil analisis data yang telah dilakukan didapatkan bahwa ada hubungan positif dan sangat signifikan antara Marital Adjustment dengan Psychological well-being.